Porphyromonas gingivalis and Treponema denticola Mixed Microbial Infection in a Rat Model of Periodontal Disease - Verma, Raj K.; Rajapakse, Sunethra; Meka, Archana; Hamrick, Clayton; Pola, Sheela; Bhattacharyya, Indraneel; Nair, Madhu; Wallet, Shannon M.; Aukhil, Ikramuddin; Kesavalu, Lakshmyya (Interdisciplinary Perspectives on Infectious Diseases, 2010)
Porphyromonas gingivalis and Treponema denticola are periodontal pathogens that express virulence factors associated with the pathogenesis of periodontitis. In this paper we tested the hypothesis that P. gingivalis and T. denticola are synergistic in terms of virulence; using a model of mixed microbial infection in rats. Groups of rats were orally infected with either P. gingivalis or T. denticola or mixed microbial infections for 7 and 12 weeks. P. gingivalis genomic DNA was detected more frequently by PCR than T. denticola. Both bacteria induced significantly high IgG, IgG2b, IgG1, IgG2a antibody levels indicating a stimulation of Th1 and Th2 immune response. Radiographic and morphometric measurements demonstrated that rats infected with the mixed infection exhibited significantly more alveolar bone loss than shaminfected control rats. Histology revealed apical migration of junctional epithelium, rete ridge elongation, and crestal alveolar bone resorption; resembling periodontal disease lesion. These results showed that P. gingivalis and T. denticola exhibit no synergistic virulence in a rat model of periodontal disease.